A Humán Tőke Indexe a Dél-Dunántúli régióban = Human Capital Index in the South Transdanubian region - Horváthné Kovács, Bernadett; Barna, Róbert; Titov, Alexander; Nagy, Mónika Zita (Közép-Európai Közlemények, 2017)
The authors addressed the spatial analysis of the humán Capital of settlements in the South Transdanubian region. It is widely agreed by researchers that especially endogenous régiónál development relies highly on local assets, among them local humán Capital. On the other hand there are several indicators in use fór measuring spatial allocation of local Capital or humán Capital without a consensus among researchers. Humán Capital has already been studied from several aspects and reviewing these studies made us confident to work on the topic further. The authors focused on the feasible development of a complex indicator which reflects the spatial allocation of humán Capital potential in the South Transdanubian region in order to identify the settlements with puliing eífect on their surrounding settlements and those areas which are either outliers or negatively affect their neighbourhoods. It was found that local humán Capital of the Southern Transdanubian settlements had to somé extent clear spatial pattems, which is mainly induced by the role of Central settlements. Although in somé cases the puliing effect of these bigger cities is nőt unambiguous, nőt all of their neighbouring settlements benefit. On the other hand, the majority of the settlements does nőt belong to either positive or negative clusters, and only a few cases were seen as outliers, too.